A displaced stress fracture of the femoral neck in an adolescent female distance runner with female athlete triad: A case report - Okamoto, S.; Arai, Y.; Hara, K.; Tsuzihara, T.; Kubo, T. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2010)
This report presents a case of a displaced stress fracture of the femoral neck in an adolescent female distance runner with amenorrhea. Both reduction and internal fixation were performed early after the injury. At 24 months postoperatively, magnetic resonance imaging and bone scintigraphy showed no positive signs of femoral head necrosis and bone union was confirmed on plain X-ray. A medical examination for the presence of the signs of the female athlete triad by checking weight, calorie intake and menstrual cycles is most important to prevent such stress fractures. Athletes as well as their coaches or parents therefore need to understand female athlete triad.